Handbook of research on sustainable development goals, climate change, and digitalization - Castanho, Rui Alexandre (Practice, progress, and proficiency in sustainability (PPPS) book series., 2022)
"In the last few years, with the world changing considerably, this book looks into the many obstacles, barriers, and opportunities pertaining to the future planning of our territories and cities to achieve the sustainable development goals taking into account climate changes and the shift towards the digitalization"--